2010
DOI: 10.1530/rep-09-0538
|View full text |Cite
|
Sign up to set email alerts
|

Use of proteomics to identify highly abundant maternal factors that drive the egg-to-embryo transition

Abstract: As IVF becomes an increasingly popular method for human reproduction, it is more critical than ever to understand the unique molecular composition of the mammalian oocyte. DNA microarray studies have successfully provided valuable information regarding the identity and dynamics of factors at the transcriptional level. However, the oocyte transcribes and stores a large amount of material that plays no obvious role in oogenesis, but instead is required to regulate embryogenesis. Therefore, an accurate picture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 84 publications
(88 reference statements)
2
56
1
2
Order By: Relevance
“…17 Maternal-effect genes are a subset of genes whose products, mRNA and proteins, are coded by the maternal genome and are stored in the oocyte to sustain normal postzygotic development until the activation of the fetal genome. 22 The maternal-effect of KHDC3L is supported by the facts that one of our patients, 481, had HMs with three different partners, and a second one, patient 654, had a high rate of postzygotic aneuploidies after two cycles of IVF performed at the age of 32. These data are in agreement with our previous observations in some patients with NLRP7 mutations 11,23 and suggest that the two genes might have similar or overlapping functions in early development.…”
Section: Discussionsupporting
confidence: 52%
“…17 Maternal-effect genes are a subset of genes whose products, mRNA and proteins, are coded by the maternal genome and are stored in the oocyte to sustain normal postzygotic development until the activation of the fetal genome. 22 The maternal-effect of KHDC3L is supported by the facts that one of our patients, 481, had HMs with three different partners, and a second one, patient 654, had a high rate of postzygotic aneuploidies after two cycles of IVF performed at the age of 32. These data are in agreement with our previous observations in some patients with NLRP7 mutations 11,23 and suggest that the two genes might have similar or overlapping functions in early development.…”
Section: Discussionsupporting
confidence: 52%
“…In this regard, the oocyte profits from a large amount of stored material that is crucial not only for the completion of oogenesis but also for embryogenesis. Proteomic analysis of mouse oocytes revealed that some abundant proteins in the ooplasm are unique to the oocyte and organized in so-called maternal-effect structures that support oocyte-to-embryo transition (Yurttas et al 2010). In view of the fast kinetics of reprogramming, we think that the oocyte may mobilize pre-stored oocyte factors having an active rather than permissive role in reprogramming.…”
Section: The Elusive Reprogramming Factorsmentioning
confidence: 98%
“…By definition, a "canonical" or "bona fide" MEG exhibits the following properties (Yurttas, Morency, & Coonrod, 2010). First, the effect of an MEG results not from zygotic inheritance of the gene from the mother or father, but rather from inheritance of the mRNA associated with that gene via the oocyte; second, MEG-knockout (MEG null) embryos gestated by normal MEG (MEG positive) mothers develop normally with the following critical exception.…”
Section: Maternal Effect Genesmentioning
confidence: 99%
“…The number of mammalian genes that have been classified as maternal effect thus far is significantly less than the number of proteins one would expect to be necessary for pre-EGA embryonic development (Yurttas et al, 2010;Zhang et al, 2009). There are potentially many reasons for this, but I will consider five.…”
Section: Maternal Effect Genesmentioning
confidence: 99%